2018
DOI: 10.4103/jnrp.jnrp_436_17
|View full text |Cite
|
Sign up to set email alerts
|

Upper Cervical Bronchogenic Cyst: A Rare Condition at a Rare Location

Abstract: Intraspinal bronchogenic cyst (SBC) is a rare but important cause of spinal cord compression, commonly seen in the cervicothoracic spine. We report a case of a 43-year-old male, presenting with complaints of neck pain, radiating to right shoulder, with numbness of right hand and fingers. Magnetic resonance imaging of the cervical spine revealed an intradural extramedullary, ventral cystic lesion extending from C2 to C4 vertebral levels. Complete surgical excision was performed, and the patient had a complete r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…MRI characteristics usually showed homogenous and hyperintense on T2WI and hypointense on T1WI ( 17 , 19 ). But enhancement was rarely after gadolinium infusion ( 11 , 18 ). According to the MRI features provided in the previous studies and the patients in our hospital, we suggested that lesions with hypointense on T1WI and hyperintense on T2WI was more common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI characteristics usually showed homogenous and hyperintense on T2WI and hypointense on T1WI ( 17 , 19 ). But enhancement was rarely after gadolinium infusion ( 11 , 18 ). According to the MRI features provided in the previous studies and the patients in our hospital, we suggested that lesions with hypointense on T1WI and hyperintense on T2WI was more common.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 27 patients were identified from the literature (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), pooled with the nine new patients described above. Table 2 shows the patient clinical baseline characteristics and radiologic findings for all 36 patients.…”
Section: Comprehensive Demographics Datamentioning
confidence: 99%